A simple method for determining the coagulation threshold temperature of transparent tissue‐mimicking thermal therapy gel phantoms: Validated by magnetic resonance imaging thermometry. Issue 3 (8th February 2016) - Brodin, N. Patrik; Partanen, Ari; Asp, Patrik; Branch, Craig A.; Guha, Chandan; Tomé, Wolfgang A.
Abstract : Purpose: Tissue‐mimicking thermal therapy phantoms that coagulate at specific temperatures are valuable tools for developing and evaluating treatment strategies related to thermal therapy. Here, the authors propose a simple and efficient method for determining the coagulation threshold temperature of transparent thermal therapy gel phantoms. Methods: The authors used a previously published gel phantom recipe with 2% (w/v) of bovine serum albumin as the temperature‐sensitive protein. Using the programmable heating settings of a polymerase chain reaction (PCR) machine, the authors heated 50 μ l gel samples to various temperatures for 3 min and then imaged them using the BioRad Gel Doc system to determine the coagulation temperature using an opacity quantification method. The estimated coagulation temperatures were then validated for gel phantoms prepared with different p H levels using high‐intensity focused ultrasound (HIFU) heating and magnetic resonance imaging (MRI) thermometry methods on a clinical MR‐HIFU system. Results: The PCR heating method produced consistent and reproducible coagulation of gel samples in precise correlation with the set incubation temperatures. The resulting coagulation threshold temperatures for gel phantoms of varying p H levels were found to be 44.1 ± 0.1, 53.4 ± 0.9, and 60.3 ± 0.9 °C for p H levels of 4.25, 4.50, and 4.75, respectively. This corresponded well with the coagulation threshold temperatures determined by MR‐thermometry, with coagulation defined as a 95% decrease in T2 relaxation time, which were estimated at 53.6 ± 1.9 and 62.9 ± 2.4 °C for a p H of 4.50 and 4.75, respectively. Conclusions: The opacity quantification method provides a fast and reproducible estimate of the coagulation threshold temperature of transparent temperature‐sensitive gel phantoms. The temperatures determined using this method were well within the range of temperatures estimated using MR‐thermometry. Due to the specific heating capabilities of the PCR machine, and the robust determination of coagulation threshold temperatures based on the statistically significant increase in the opacity of gel samples, coagulation temperatures can be determined more precisely and with less variability compared to MRI‐based methods.